Edukasi Pemanfaatan Sabut Kelapa menjadi Cocopeat Sebagai Inovasi Bernilai Ekonomi di Dusun Karya Utama Desa Sungai Belidak - Ilzar Daud; Fadila Ramadanti; Revalin Zalianty; Ctherine Felancia Evelyn; Erlina Putri Febrianti; Deshinta Prameswari Diana Putri (Pusat Riset dan Inovasi Nasional, 2025)
This community service was conducted in Karya Utama Hamlet, Sungai Belidak Village, Kubu Raya Regency, West Kalimantan, aiming to utilize coconut husk waste into cocopeat as an eco-friendly and economically valuable planting medium. Previously, residents mostly discarded or burned coconut husks, causing environmental issues. The program began with surveys, followed by seminars, training, and interactive discussions on the benefits, production process, and business opportunities of cocopeat. Results showed improved knowledge, skills, and awareness among the community in processing waste into marketable products. The training output, Tacokaru (tanah cocopeat karya utama), was tested on chili plants and demonstrated positive growth. Socially, the program encouraged behavioral change, strengthened community cohesion, and opened business opportunities. With support from the village government and e-commerce utilization, this initiative shows strong sustainability potential as a local eco-friendly business while empowering the rural economy.